Financial Development and Economic Sustainability in ECOWAS Countries: the Role of Institutional Quality - Fanglin Li; Michael Appiah; Benjamin Korankye (ETIKONOMI, 2020)
The literature explored the relationship between financial development and economic sustainability, taking into consideration the roles played by institutional quality in the ECOWAS region. Most literature still debates on the roles of institutional quality on economic growth. The study used data from 1996-2017 for 15 emerging economies within the ECOWAS by applying two-step SYS GMM (SGMM) estimators.  The study discovered that financial development has no significant and positive alliance on economic sustainability in the ECOWAS region. Besides that, regulatory quality and control of corruption, considered institutional quality variables have conflicting results with control of corruption reducing growth as well as regulatory quality increasing growth. Again, the results came out that capital formation has a positive association with growth and labor force influencing negatively on growth.  Finally, due to a lack of proper corruption control systems in the region and poor financial sector development, growth cannot improve.JEL Classification: O11, O43, C23How to Cite:Li, F., Appiah, M., & Korankye, B. (2020). Financial Development and Economic Sustainability in ECOWAS Countries: The Role of Institutional Quality. Etikonomi: Jurnal Ekonomi, 19(1), 41 – 50. https://doi.org/10.15408/etk.v19i1.13709.